The System of Cholesterol Determination in Humans byy Iridology Edge Detection - . Saefurrohman (Dinamik, 2013)
Iridology provided special perspective to the concept of health and medical practices. Only by observation from outside the body, namely check for signs of an iris iridology idiomatic condition would be revealed by the organ and tissue in the body system, long before clinical symptoms of an illness experienced by a person may feel or diagnosed by conventional methods Required analytical methods for measuring and determining cholesterol in the human body, by testing the Sobel edge detection, Prewitt and Robert Canny edge detection realized in a software help to define or classify normal cholesterol levels, moderate to high cholesterol levels in the human body. Introduction of the iris database features Matching method by distance classifier based on the results of segmentation, edge detection, semi-polarization and the quantization able to detect the level of cholesterol in the human body ranges up to 80% of the 90 samples. Keywords: Iridology, edge detection, distance classifier, semi-polarization, quantization